The Sec1p/Munc18 (SM) protein, Vps45p, cycles on and off membranes during vesicle transport - Bryant, Nia J. (The Rockefeller University Press, 2003)
Protein phosphatase 1 (PP1, Glc7p) functions in the final stage of SNARE-mediated vesicle transport between docking and fusion. During this process, trans-SNARE complexes, formed between molecules in opposing membranes, convert to cis-complexes, with all participants in the same lipid bilayer. Here, we show that glc7 mutant cells accumulate SNARE complexes. These complexes are clearly different from those found in either wild-type or sec18–1 cells as the Sec1p/Munc18 (SM) protein Vps45p does not bind to them. Given that PP1 controls fusion, the SNARE complexes that accumulate in glc7 mutants likely represent trans-SNARE complexes. Vps45p dissociates from the membrane in the absence of PP1 activity, but rapidly reassociates after its reactivation. These data reveal that SM proteins cycle on and off membranes in a stage-specific manner during the vesicle transport reaction, and suggest that protein phosphorylation plays a key role in the regulation of this cycle.